Uma estratégia para introduzir pipelines de IC em disciplinas de resolução de problemas V - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Configuring Continuous Integration (CI) pipelines is a complex and crucial task in configuration management practices. It requires software engineers to have the technical skills to configure CI servers or services. These professionals need to select knowledge-intensive resources to automate software processes. In the context of configuration management, this means having the ability to transform these resources into Continuous Integration, Deployment and Delivery tasks, organized into pipelines. This skill requires specialized knowledge of tools for managing configurations in various software projects. The search for this knowledge is one of the objectives of the Problem Solving (PR) subjects, especially RP 5, in the Bachelor’s degree course in Software Engineering at Unipampa. Motivated by this need, this Capstone explores the difficulties students face in configuring CI pipelines and proposes a teaching strategy. The main contributions of this TCC are: 1) a source code repository mining study, derived from the RP 5 course and carried out in 2018; 2) a longitudinal survey of students from four editions of this course (2015, 2016, 2017 and 2018), which highlights the need for a teaching strategy that includes elements of configuration management; 3) a systematic mapping study of the literature on the subject, which highlights the state of the art and positions this TCC in terms of innovation; 4) a practical analysis of CI servers/services and their configuration syntaxes, with the aim of motivating students by presenting examples of pipelines at three levels of difficulty; 5) a strategy for students and teachers to introduce CI pipelines in RP courses; and 6) a report on the implementation of this strategy in RP course 5, which took place in 2021. Key-words: continuous integration . CI. Pipeline.
Keywords: Engenharia de software; Integração contínua; Pipeline; Software engineering; Continuous integration; CNPQ::CIENCIAS EXATAS E DA TERRA